2021
DOI: 10.1080/21645515.2021.1965424
|View full text |Cite
|
Sign up to set email alerts
|

How were DTP-related adverse events reduced after the introduction of an acellular pertussis vaccine in Chile?

Abstract: Chile has a passive surveillance system of adverse events following immunization (AEFI) that allows monitoring and evaluating the safety profile of the vaccines administered. Between 2018 and 2019, the National Immunization Program (NIP) changed from a pentavalent whole-cell pertussis vaccine (wP) to a hexavalent (DTaP-IPV-HepB-Hib) acellular pertussis vaccine (aP) for children <2 years. Objectives: To describe the trend in the frequency of adverse events (AE) records associated to pertussis component vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…The male-to-female ratio of reported AEFIs for DTaP, DTaP-Hib, and DTaP-IPV/Hib was 1.27:1, 1.05:1, and 0.95:1, respectively. The reporting rate of DTaP was higher than the levels reported in Chile ( 17 ), while the reporting rate of DTaP-IPV/Hib was lower than in other regions ( 28 ). The reporting rates of AEFIs for DTaP and DTaP-IPV/Hib were highest in the ≥18 months age group.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The male-to-female ratio of reported AEFIs for DTaP, DTaP-Hib, and DTaP-IPV/Hib was 1.27:1, 1.05:1, and 0.95:1, respectively. The reporting rate of DTaP was higher than the levels reported in Chile ( 17 ), while the reporting rate of DTaP-IPV/Hib was lower than in other regions ( 28 ). The reporting rates of AEFIs for DTaP and DTaP-IPV/Hib were highest in the ≥18 months age group.…”
Section: Discussioncontrasting
confidence: 63%
“…A major challenge to the safety of the DTaP combination vaccine is that the vaccine needs to be administered in early infancy. To assess the safety and effective administration of vaccines, especially when new vaccines are introduced in any country, WHO recommends that countries should establish effective AEFI reporting programs ( 17 ). The AEFI surveillance are conducted by either applying a passive or active approach to monitor vaccine safety in various countries ( 22–24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies reported on 830,585,553 doses of COVID-19 vaccines, 3,23-44 3 studies reported on 154,220,042 doses of HPV vaccines, 6,45,46 5 studies on 513,115,509 doses of influenza vaccines, 25,47-50 2 studies on 4,952,349 doses of acellular pertussis vaccines, 51,52 3 studies on 1,386,209 doses of smallpox vaccines, 50,53,54 and 2 studies on 24,200,000 doses of mixed vaccines (epidemic cerebrospinal meningitis and pneumococcal conjugate vaccine). 55 In the 23 studies involving COVID-19 vaccination, 647,308,174 doses of mRNA vaccines and 183,238,205 doses of non-mRNA vaccines were administered.…”
Section: Resultsmentioning
confidence: 99%
“…Many countries have switched from wP- to aP-containing vaccines due to the lower reactogenicity of the latter ( 17 ). Low reactogenicity (i.e.…”
Section: Benefits Of Introducing Hexavalent Acellular Pertussis–inact...mentioning
confidence: 99%